1988
DOI: 10.1111/j.1365-2222.1988.tb02851.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of atopy on the clinical manifestations of coronavirus infection in adult volunteers

Abstract: Summary In an attempt to understand the relationship between viral upper respiratory tract infection and the underlying virological and immunological mechanisms, thirty‐four volunteers were inoculated intranasally with coronavirus 229E; subsequent virus shedding and/or antibody rises, indicating active infection, were observed in twenty‐nine. There was a greater increase in independently measured scores of clinical severity, e.g. cold symptoms, in those with detectable IgE in nasal secretions (P < 0.01). A sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Could similar mechanisms account for the beneficial effect, shown here, of nedocromil sodium on the symptomatology of experimental colds? The recent study reported by the Common Cold Unit failed to show raised levels of LTB4 and LTC4 or histamine [8], mediators which have been implicated in asthma, in the nasal secretions of subjects following viral inoculation. However, the inability to detect these mediators by direct methods does not exclude them from playing a role, albeit minor, in the common cold.…”
Section: Discussion mentioning
confidence: 85%
See 1 more Smart Citation
“…Could similar mechanisms account for the beneficial effect, shown here, of nedocromil sodium on the symptomatology of experimental colds? The recent study reported by the Common Cold Unit failed to show raised levels of LTB4 and LTC4 or histamine [8], mediators which have been implicated in asthma, in the nasal secretions of subjects following viral inoculation. However, the inability to detect these mediators by direct methods does not exclude them from playing a role, albeit minor, in the common cold.…”
Section: Discussion mentioning
confidence: 85%
“…Pharmaceutical Division, Loughborough. Leicestershire LEI 1 ORH, U.K. sible for part or all of the inflammatory response to viral infection of the upper respiratory tract have been unsuccessful or at best inconclusive [8][9][10]. The aim of the present studies was to investigate the effect of nedocromil sodium on symptoms resulting from infection with two different respiratory viruses.…”
Section: Introductionmentioning
confidence: 97%
“…It was also possible to document the way viruses damage cilia and slow mucociliary transport (Wilson et al, 1989) to look for the role of atopy and possible mediators in producing respiratory symptoms (Callow et al, 1988) and to document local physiological parameters such as nasal blood flow (Bende et al, 1989). Psychological factors, such as personality and 'stress' were also found to be important.…”
Section: Searching For Prevention or Treatmentmentioning
confidence: 99%
“…We do not have equally precise information for colds. Rather low amounts of leukotrines, prostaglandins and histamine have been found in nasal secretions in colds (Callow et al, 1988) and blocking cholinergic transmission has limited effect on cold symptoms (Gaffey et al, 1988). On the other hand an inhibitor of mast cell degranulation, which impedes mediator release, has some beneficial effect on colds -even though this has not been proved to be due to an effect on mediators (Barrow et al, 1990a).…”
Section: (5) Blockers Of Mediatorsmentioning
confidence: 99%
“…Attempts to demonstrate the presence of certain mediators of tissue reaction to infection, e.g. histamine and leukotrienes, in the nasal secretions of individuals with colds have proved negative or, at best, equivocal (Egglestone et al, 1984;Naclerio et al, 1987;Callow et al, 1988;Proud et al, 1990). However, kinins, including bradykinin, have been shown to be generated during the coryzal phase of both experimental (Naclerio et al, 1987) and natural (Proud et al, 1990) rhinovirus infections and the intranasal administration of bradykinin produces symptoms indistinguishable from those of a rhinovirus cold (Proud et al, 1988).…”
Section: Introductionmentioning
confidence: 99%